Sistem Terintegrasi Pengendali Rumah-Rumah Pintar Berbasis Android - Wibowo Harry Sugiharto; Ahmad Abdul Chamid (Jurnal Mantik Penusa, 2018)
The smart home is a system that aims to change a home has an automation control to increase users comfort, security and energy conservation. The smart home system generally stands alone, there is no integrated system that brings together smart homes. This study is used to build a smart home that is connected between one house and another house, that is, one house can be controlled by one or more houses or can be used by one user, as long as the user has access rights to the controlled house. The design system is used a central server which will be accessed by users to control the houses. Users can control via an Android-based application that is connected to a central server. Keywords: Integrated System, Smart Home, Android Application